MCSE lab manual for Microsoft Windows 2000 server - Carswell, Ron (Course Technology, 2001)
The microsoft windows 2000 server lab manual provides you with the hands-on instruction you'll need for success as a windows 2000 network administrator or network support professional. Designed for classroom-led pr self-paced study, these labs offer a unique, hands-on approach to learning that is a key component to the windows 2000 MCSE exams.